2021
DOI: 10.1186/s40643-021-00441-y
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent production of glycyrrhetic acid 3-O-mono-β-d-glucuronide and lignocellulolytic enzymes by solid-state fermentation of a plant endophytic Chaetomium globosum

Abstract: Glycyrrhetic acid 3-O-mono-β-d-glucuronide (GAMG) as an important derivative of glycyrrhizin (GL) shows stronger biological activities and higher sweetness than GL. The biotransformation process is considered as an efficient strategy for GAMG production, due to its mild reaction, high production efficiency and environmentally friendly status. In this study, licorice straw was used for the first time as a medium for GAMG and lignocellulosic enzyme production via solid-state fermentation (SSF) of endophytic fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Endophytic fungi are an ecological group of fungi that inhabit the tissues and organs of healthy plants, without causing any external symptoms of the host plant (Staniek et al, 2008). In last decades, endophytic fungi have been attracted more and more attention due to its excellent capacity for secreting a diverse array of bioactive compounds and enzymes (Higginbotham et al, 2013;Suryanarayanan et al, 2012;Gao et al, 2021;Xiao et al, 2022). Recently, some studies have found that plant fungal endophytes exhibit excellent properties in bioconversion of natural saponin, such as glycyrrhizic acid (Gao et al, 2021;Xiao et al, 2022), ginsenosides (Eom et al, 2018), with high activity and substrate speci city.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic fungi are an ecological group of fungi that inhabit the tissues and organs of healthy plants, without causing any external symptoms of the host plant (Staniek et al, 2008). In last decades, endophytic fungi have been attracted more and more attention due to its excellent capacity for secreting a diverse array of bioactive compounds and enzymes (Higginbotham et al, 2013;Suryanarayanan et al, 2012;Gao et al, 2021;Xiao et al, 2022). Recently, some studies have found that plant fungal endophytes exhibit excellent properties in bioconversion of natural saponin, such as glycyrrhizic acid (Gao et al, 2021;Xiao et al, 2022), ginsenosides (Eom et al, 2018), with high activity and substrate speci city.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, these enzymes secreted, which are used for plant tissue invasion, colonization, and nutrient acquisition by endophytic fungi, make them a valuable source of biocatalysts for the biotransformation of natural products. (Higginbotham et al 2013 ; Suryanarayanan et al 2012 ; Gao et al 2021 ; Xiao et al 2022 ). Recently, some studies have found that plant fungal endophytes exhibit excellent properties in bioconversion of natural saponin, such as glycyrrhizic acid (Gao et al 2021 ; Xiao et al 2022 ), ginsenosides (Eom et al 2018 ), with high activity and substrate specificity.…”
Section: Introductionmentioning
confidence: 99%
“…(Higginbotham et al 2013 ; Suryanarayanan et al 2012 ; Gao et al 2021 ; Xiao et al 2022 ). Recently, some studies have found that plant fungal endophytes exhibit excellent properties in bioconversion of natural saponin, such as glycyrrhizic acid (Gao et al 2021 ; Xiao et al 2022 ), ginsenosides (Eom et al 2018 ), with high activity and substrate specificity. Indeed, fungal endophytes have been suggested as high-efficient biocatalyst sources, revealing great potential application in medicine, food security, and social sustainability (Schulz et al 2002 ; Suryanarayanan et al 2012 ; Choudhary et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical synthesis of GAMG suffers from complicated process, high cost, and environmental pollution ( Guo et al, 2018 ). Recently, GAMG and lignocellulosic enzyme were produced by the licorice straw as a medium for via solid-state fermentation (SSF) of endophytic fungus Chaetomium globosum DX-THS3( Gao et al, 2021 ), however the 90% GL transformed to GAMG needs 15 days. Currently, biotransformation with GL as the substrate is the major approach for GAMG production, unfortunately not fully addressing the source and environmental damage concerns.…”
Section: Introductionmentioning
confidence: 99%